Soil Moisture Conservation in Dryland Viticulture as affected by Conventional and Minimum Tillage Practices - Van Huyssteen, L.; Weber, H. W. (South African Journal of Enology and Viticulture, 2017)
The effect of conventional clean cultivation, a straw mulch, chemical weed control and a grass sward on the soil moisture regime in a dryland vineyard was investigated. The results demonstrate that both a straw mulch and chemical weed control were very effective ju conserving winter-stored soil moisture until mid- or even late summer to support the vines during the almost rainless growing season. Further, it appeared that a mere loosening of the soil surface periodically by way of clean cultivation cannot conserve soil moisture effectively; it may, on the contrary, promote evaporation in the top-soil layers, especialzy when done after rain. On the other hand, an undisturbed soil surface, as in the case of chemical weed control, acts as a mulch in itself after the surface layer has dried out, thus reducing evaporation. Even under conditions of frequent rainfall, as during the first part of 1976/77 season, the straw mulch cover treatment was still superior to all other treatments in conserving soil moisture.